Quinazolines and quinazolinones as ubiquitous structural fragments in medicinal chemistry: An update on the development of synthetic methods and pharmacological diversification. Issue 11 (1st June 2016) - Khan, Imtiaz; Zaib, Sumera; Batool, Sadaf; Abbas, Naeem; Ashraf, Zaman; Iqbal, Jamshed; Saeed, Aamer
Graphical abstract: The current review article is an update to the recent developments in synthetic methodologies for the construction of quinazoline and quinazolinone heterocycles. Mechanistic investigations, synthetic and pharmacological applications have also been discussed. Highlights: Quinazolines and quinazolinones are useful bioactive scaffolds in medicinal chemistry. Mild, efficient and environmentally benign synthetic procedures. Mechanistic investigations and synthetic applications. Pharmaceutical and agrochemical applications. Abstract: Nitrogen-rich heterocycles, particularly quinazolines and quinazolinones, represent a unique class of diversified frameworks displaying a broad spectrum of biological functions. Over the past several years, intensive medicinal chemistry efforts have generated numerous structurally functionalized quinazoline and quinazolinone derivatives. Interest in expanding the biological effects, demonstrated by these motifs, is growing exponentially, as indicated by the large number of publications reporting the easy accessibility of these skeletons in addition to the diverse nature of synthetic as well as biological applications. Therefore, the main focus of the present review is to provide an ample but condensed overview on various synthetic approaches providing access to quinazoline and quinazolinone compounds with multifaceted biological activities. Furthermore, mechanistic insights, synthetic utilization, structure–activity relationships and molecular modeling inputs for the potent derivatives have also been discussed.